2020
DOI: 10.1093/nsr/nwaa247
|View full text |Cite
|
Sign up to set email alerts
|

Pathological changes in the lungs and lymphatic organs of 12 COVID-19 autopsy cases

Abstract: Systematic autopsy and comprehensive pathological analyses of COVID-19 decedents should provide insights into the disease characteristics and facilitate the development of novel therapeutics. In this study, we report the autopsy findings from the lungs and lymphatic organs of twelve COVID-19 decedents that evaluated histopathological changes, immune cell signature, and inflammatory factor expression in the lungs, spleen, and lymph nodes. Here we show that the major pulmonary alternations included diffuse alveo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 26 publications
3
71
0
2
Order By: Relevance
“…In another study, Liu et al reported that the postmortem spleens were generally contracted with shrinking capsules, mixed thrombi, hemorrhage, and anemic infarction. Moreover, COVID-19 spleens showed a prominent absence of lymphoid follicles as compared to control spleens from patients with abdominal trauma necessitating splenectomy [95] ; further highlighting the deteriorating effect of SARS-CoV-2 on the spleen. Elsoukkary.…”
Section: Pathophysiology For Lymphopenia In Covid-19mentioning
confidence: 90%
“…In another study, Liu et al reported that the postmortem spleens were generally contracted with shrinking capsules, mixed thrombi, hemorrhage, and anemic infarction. Moreover, COVID-19 spleens showed a prominent absence of lymphoid follicles as compared to control spleens from patients with abdominal trauma necessitating splenectomy [95] ; further highlighting the deteriorating effect of SARS-CoV-2 on the spleen. Elsoukkary.…”
Section: Pathophysiology For Lymphopenia In Covid-19mentioning
confidence: 90%
“…Moreover, in several cases, spleens showed atrophic white pulp and relatively enlarged red pulp ( Figure 3 A). Finally, some of the COVID-19 spleens had a reduced number of CD20-positive B lymphocytes (100%) compared to controls [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of lymphoid organ involvement, T-cell depletion occurred in the spleen [ 169 ]. Necrosis or atrophy in the lymphoid tissue of lymph nodes and white pulp of the spleen are commonly observed extrapulmonary pathologies [ 170 ].…”
Section: Histopathology and Pathogenesis Of Covid-19mentioning
confidence: 99%